Contributions of Brigada eskwela to the improvement and sustainability of school structures and facilities in Bangui district, Bangui, Ilocos Norte - Ragasa, Blesilda Constancia (Laoag City : [s.n.], 2012)
This study determined the contributions of the Brigada Eskwela (BE) program to improvement and sustainability of physical structures and facilities of elementary schools in Bangui District, Division of Ilocos Norte. The study employed the descriptive-correlational research design using a questionnaire in gathering data from all the eight school administrators and 99 randomly selected teachers of Bangui District who served as respondents. The mean, weighted mean, frequency and percentage were used to describe the data gathered while the simple linear regression analysis was used to determine the contributions of the Brigada Eskwela (BE) program to improvement and sustainability of school structures and facilities.
Bibliography: page 88.
CHED-La Union
Keywords: Schools -- Equipment and supplies